A Study on Electrical Characterization of Surface Potential and Threshold Voltage for Nano Scale FDSOI MOSFET - Shakher Tyagi, Chandra; L. Sharma, R; Mani, Prashant (International Journal of Engineering and Technology, 2018)
In this paper the study of electrical characterization of Surface potential & Vth threshold-voltage model is developed for FD SOI MOSFET. The threshold voltage is important parameter in device design. Scaling of device has positive impact on device performance. The various parameters like thickness of silicon film, oxide layer, drain to source voltage plays a key role in improvement of device performance. Surface potential explain the distribution of applied potential throughout the channel. We also analyzed the effect of threshold voltage with various electrical parameters.Â Â Â